An examination of autopsies in a 400 bedded government hospital in Jhelum. An insight into the sudden cause of death and costs associated with autopsy in young government personnel - Naeem, Uzma; Qamar Uddin Khan; Iftikhar Ahmed Satti; Afshan Bibi (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the different causes of sudden death among serving government employees. Method: The audit study was conducted at the Pathology Department of a tertiary care hospital Combined Military Hospital (CMH) Jhelum, Pakistan, and comprised data of all autopsies between January 2017 and June 2021. Sampling technique was non probability purposive sampling technique which requires no statistical method calculation. Data was recorded related to weight of specimens, lists of tissue specimens for histopathological, chemical, and forensic examination, and the tests performed on samples of blood, urine, and other body fluids. Ethical review approval was taken from ethical review committee of the hospital dated October 2017. Data was analysed using Microsoft excel. Results: All the 34 autopsies of male subjects were performed to explore the cause of sudden death. Coronary atherosclerosis was the most common cause of death 14(41.2%), followed by drowning 4(11.7%). Drug abuse, blood alcohol, narcotics, carbon monoxide and toxic elements were found in 5(14.7%) cases. Conclusion: Myocardial infarction was found to be the most common cause of death among serving government employees. Key Words: Autopsy, Coronary atherosclerosis.